The optimization of in vitro sterilization on Ebony (Diospyros celebica Bakh) using shoot explants. Issue 1 (October 2020) - Dalauleng, A; Gusmiaty,; Panannangan, F D; Restu, M
Abstract: Ebony ( Diospyros celebica Bakh ) is a woody plant that has been used in the manufacture of luxury veneers, plywood, luxury furniture, sculpture, carving decorative tools, sticks, piano guitars, wind instruments and building materials. To maintain the existence of Ebony, it is necessary to provide good seedling quality through the tissue culture method. Tissue culture is one of the clonal propagation techniques for mass propagation. Moreover, it is able to produce a large quantity of plants in a relatively short time and obtain superior seedling. The process of sterilizing plant material (explants) is an important activity in tissue culture which aims to eliminate microorganisms carried during explant extract, which can cause contamination. This study aimed to obtain the optimal sterilization procedure for Ebony in vitro micropropagation. The analysis used was descriptive analysis by observing the percentage of contaminated explants, types of contamination, and explants that had browned (browning). Sterilization using Bactericides and Fungicides showed the lowest contamination level (71%). There were three types of contamination found, namely fungal contamination, bacterial contamination, and a combination of fungal and bacterial contamination. The lowest percentage of browning explants was using sterilization 3 (71%).